2021
DOI: 10.3390/metabo11110727
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Changes in Naturally MAP-Infected Holstein–Friesian Heifers Indicate Immunologically Related Biochemical Reprogramming

Abstract: Johne’s disease, caused by Mycobacterium avium subsp. paratuberculosis (MAP), causes weight loss, diarrhoea, and reduced milk yields in clinically infected cattle. Asymptomatic, subclinically infected cattle shed MAP bacteria but are frequently not detected by diagnostic tests. Herein, we compare the metabolite profiles of sera from subclinically infected Holstein–Friesian heifers and antibody binding to selected MAP antigens. The study used biobanked serum samples from 10 naturally MAP-infected and 10 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 68 publications
(80 reference statements)
4
17
1
Order By: Relevance
“…Our findings identified 11 metabolites in MAP-inoculated heifer calves that were also observed in our Taylor et al [ 16 ] study which focused on natural MAP infections. The prominence of metabolites from the fatty acyl class and fatty acids and conjugates subclass, alongside the eicosanoid subclass was notable in both studies (Additional file 2 ) [ 16 ]. However, there was an absence of metabolites belonging to the amino acids, peptides and analogues subclass in our current study (Additional file 2 ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our findings identified 11 metabolites in MAP-inoculated heifer calves that were also observed in our Taylor et al [ 16 ] study which focused on natural MAP infections. The prominence of metabolites from the fatty acyl class and fatty acids and conjugates subclass, alongside the eicosanoid subclass was notable in both studies (Additional file 2 ) [ 16 ]. However, there was an absence of metabolites belonging to the amino acids, peptides and analogues subclass in our current study (Additional file 2 ).…”
Section: Discussionsupporting
confidence: 84%
“…However, no omic study has assessed MAP infection associated changes in youngstock. Our previous metabolomic study identified 33 metabolites which were differentially accumulated within naturally MAP-infected heifer calves, including 5 metabolites which were elevated throughout the study [ 16 ]. In this study, we examined experimentally MAP-inoculated heifer calves to more clearly assess early changes occurring following infection and to validate the previously observed metabolites changes in an analogous study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In details, the metabolomics studies, carried out on experimentally MAP-infected cattle using 1 H nuclear magnetic resonance (NMR) spectrometry, showed metabolomics changes related to energy shortages, increased fat metabolism, and altered protein turnover (12). Taylor et al examined the sera metabolic pro les of naturally MAP-infected Holstein-Friesian heifers and compared them to controls, nding changes in some metabolites related to biochemical reprogramming (16,17). In our previous study, we applied direct analysis in real time high resolution mass spectrometry (DART-HRMS) coupled to a midlevel data fusion approach to tease out molecular features able to chemically characterize the animal sera at the MAP preclinical stage (15).…”
Section: Introductionmentioning
confidence: 99%